Use of abatement cost curves in developing environmental bubble policy for managing SPM in Jamshedpur region. (7th September 2004) - Gupta, V.B.; Kumar, Vinay; Shah, K.K.; Gupta, Rekha; Gupta, H.K.l; Kumari, Ranju
This paper evaluates environmental bubble policy using abatement cost curves drawn for different abatement measures in Jamshedpur region. Surveys were conducted to estimate industrial emissions of suspended particulate matter (SPM) from different emitting sources in the region, and the characteristics of the existing and alternative abatement devices for each emitting source. The abatement cost functions were developed and used to rank the abatement devices. An environmental bubble with its limit equal to the existing SPM emissions from all selected companies was developed. The abatement costs for the bubble were estimated from abatement cost curves with alternative and best available technologies. The estimated abatement costs were found to be less than those of the existing measures. It was also found that M/s TISCO alone can account for SPM emissions reductions in the selected group with less cost.